Experimental Method on “Pseudo Delights” Artwork - Fransisca Retno Setyowati Rahardjo (Graduate School of Institut Seni Indonesia Yogyakarta, 2019)
ABSTRACTIn 1975 Indonesian contemporary art was believed to be born and marked by the occurrence of the “Black December” event which then initiated the Gerakan Seni Rupa Baru Indonesia. Arts academy also swiftly respond to this phenomenon by putting an art experimentation course as their subject in ITB and ASRI Yogyakarta. Another example was made in 1987, a successful experimental exhibition “Pasaraya Dunia Fantasi” which was held Taman Ismail Marzuki being a headline. It is now four decades the development of experimentation medium celebrated even to other non-art disciplines. Being consider of it the author seeks to bring back the methods of the past that have been adapted to the contexts of today's problems and technological advances. In this research will be a study to develop experimentation model by using some reference logic theory such as design thinking method to produce a work. The development of contemporary art and design has not been widely recognized as an interdisciplinary area that could potentially be developed into a sophisticated and cutting-edge work. In contrast, in some academic and art academic discourses, student’s views are narrowed by thickening the barriers between art and design under the pretext of need capitalization of education. Therefore, the author tries to create a method of designing an experimentation work entitled 'Pseudo Delights'. This work has been previously executed and exhibited at the National Gallery. Pseudo Delight is a performative event specially engineered to respond to today's hyper-reality phenomenon. Where the development of information and mass media is celebrated massively. The rise of many social media applications such as Instagram, the urban communities can celebrate the exclusivity of their lives in a virtual gallery freely. As to convince others about the image of their modern life that is considered successful often the image that appears then contain excessive payload or false sign. Something paradoxical to the advancement of information technology today is presenting a lot of fake images has become the era of the death of information itself. ABSTRAK Pada tahun 1975 seni rupa kontemporer Indonesia diyakini lahir dengan tanda hadirnya peristiwa “Black December” yang kemudian mengawali Gerakan Seni Rupa Baru Indonesia. Akademi seni juga dengan cepat merespon fenomena ini dengan menambahkan mata kuliah eksperimentas seni sebagai salah satu subjek pendidikan seni di ITB dan ASRI Yogyakarta. Contoh lain ada pada tahun 1987 ketika sebuah pameran eksperimental yang sukses